Induction and Suppression of Innate Antiviral Responses by Hepatitis A Virus - Cao, Xin; Xue, Yu-jia; Du, Jiang-long; Xu, Qiang; Yang, Xue-cai; Zeng, Yan; Wang, Bo-bo; Wang, Hai-zhen; Liu, Jing; Cai, Kui-zheng; Ma, Zhong-ren (Frontiers in Microbiology, 2018)
Hepatitis A virus (HAV) belongs to the family Picornaviridae, which causes acute viral hepatitis by fecal-oral transmission. RNA viruses were sensed by pathogen-associated pattern recognition receptors (PRRs), such as Toll-like receptor 3 (TLR3), retinoic acid-inducible gene I (RIG-I), and melanoma differentiation- associated gene 5 (MDA5). PRRs activation leads to production of Type 1 interferon (IFN-α/β), which serves as the first line to defend against viruses. However, HAV has developed various strategies to evade the innate immune system and promote viral replication inside the host cells. The long co-evolution of HAV in hosts has promoted the development of effective immune evasion strategies that actively counteract host antiviral responses. Proteases encoded by HAV can cleave mitochondrial antiviral signaling protein (MAVS, also known as IPS-1, VISA or Cardif), TIR domain- containing adaptor inducing IFN-β(TRIF, also known as TICAM-1) and nuclear factor-κB (NF-κB) essential modulator (NEMO), which are key adaptor proteins in RIG-I-like receptor (RLR), TLR3 and NF-κB signaling, respectively. In this mini-review, we summarize all the recent progress on the interaction between HAV and host, especially focusing on how HAV abrogates the antiviral effect of innate immune system.